SWOT ANALYSIS OF HOT SPRING TOURISM MANAGEMENT IN LEILEM VILLAGE, MINAHASA REGENCY - Jolanda Esther Kaihatu; Aghata Archenta Tumengkol (Universitas Sebelas Maret (UNS), 2025)
Leilem Hot Spring is a popular tourist destination with unique geothermal features and attractions. However, managing this destination requires a targeted approach so that its development runs on target and sustainably. This study identifies and analyses internal and external factors in managing Leilem Hot Springs in Minahasa Regency. A descriptive qualitative method was employed, with data collected through interviews, field observations, and documentation. Respondents were selected by accidental sampling, involving tour managers and visitors. Data analysis was conducted using the SWOT method, supported by the IFAS and EFAS matrices. The results showed an IFAS value of -(0.45), reflecting the dominance of internal weaknesses, and an EFAS of +(2.02), indicating significant external opportunities. Based on these findings, the tourist destination of Leilem Village Hot Springs, Minahasa Regency, is in a suitable position to implement a turnaround strategy through the W-O (Weaknesses-Opportunities) approach. This strategy is directed at strengthening professional management, improving facilities through synergy between stakeholders, involving the community in infrastructure improvements, and integrated promotion to expand market reach, especially in the digital era. Although the threat factor (T) is not prioritised in strategic decision-making, the issues of climate change and natural disaster risks remain critical. Managing these external factors requires integrating adaptive management based on risk mitigation and ecological principles, especially in geothermal tourism. Overall, this approach supports resource conservation, socioeconomic sustainability, and visitor safety, ensuring that natural tourism destinations remain resilient and sustainable over the long term.